Simultaneous retrieval of body and surface waves in the Dehdasht area, Iran, from the seismic ambient field and the observation of spurious artefacts. Issue 2 (12th July 2021) - Riahi, Ali; Shomali, Zaher-Hossein; Obermann, Anne; Kamayestani, Ahmad
SUMMARY: Recent developments in sensor technology have allowed for the low-cost deployment of dense seismic arrays which continuously record the seismic ambient noise field. Generally, the extraction of body waves from the seismic ambient noise field is more challenging than for surface waves, due to the dominant amplitude of the latter. In this study, we work with data from a dense seismic array deployment in the Dehdasht area, southwestern Iran. We show that by using the polarization properties of seismic waves, we can simultaneously retrieve both high frequency body waves and surface waves from the cross-correlated noise field. As a by-product of this study, we also observe high energy spurious artefacts, particularly those associated with the direct P -phases. Numerical simulations show that these artefacts are a consequence of an uneven distribution of noise sources, and are difficult to suppress during the simultaneous retrieval of body and surface waves.